2013
DOI: 10.1155/2013/643403
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Sensory and Motor Neurons Associated with BL40 and GB30 in the Rat: A Dual Fluorescent Labeling Study

Abstract: The purpose of this study is to investigate the specific innervations on “Weizhong” (BL40) and “Huantiao” (GB30) by using a dual neural tracing technique. After Alexa Fluor 488 and 594 conjugates of cholera toxin subunit B (AF488/594-CTB) were, respectively, injected into BL40 and GB30 in the same rat, the labeled sensory and motor neurons were examined in the rat's dorsal root ganglia (DRGs) and spinal cord at thoracic (T) and lumbar (L) segments with a laser scanning confocal microscope. In the cases of BL40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(14 reference statements)
1
12
0
1
Order By: Relevance
“…Previous studies from our laboratory have provided experimental evidence that motor and sensory neurons in the vicinity of classical acupuncture points follow a segmental pattern in the nervous system. 14 15 17 In the present study, we have confirmed that this is also true of acupuncture point LI11, while further demonstrating that the motor neurons of the deep tissue layer spread over a greater number of spinal segments and outnumber those of the superficial tissue layer. Although the sensory neurons associated with both deep and superficial tissue layers distribute similarly across the same spinal segments, the number of sensory neurons in the superficial tissue layer is greater than that of the deep tissue layer.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Previous studies from our laboratory have provided experimental evidence that motor and sensory neurons in the vicinity of classical acupuncture points follow a segmental pattern in the nervous system. 14 15 17 In the present study, we have confirmed that this is also true of acupuncture point LI11, while further demonstrating that the motor neurons of the deep tissue layer spread over a greater number of spinal segments and outnumber those of the superficial tissue layer. Although the sensory neurons associated with both deep and superficial tissue layers distribute similarly across the same spinal segments, the number of sensory neurons in the superficial tissue layer is greater than that of the deep tissue layer.…”
Section: Discussionsupporting
confidence: 80%
“…It is a technical limitation that AF488-CTB cannot be used to label nerve fibres and axonal terminals like conventional CTB; 17 however, it remains an appropriate method to label sensory and motor neurons associated with acupuncture points in a retrograde manner. 14 15 Although, in the present study, the tracer was separately injected into the muscle or subcutaneous tissue in the experimental animals (through the use of a skin incision), in clinical practice the acupuncture needle will always pierce the dermal layer before reaching the muscle layer. Therefore, when evaluating the effect of deep needling, the neuroanatomical characteristics associated with both the muscle and the subcutaneous tissue layers should be considered together.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…신경추적자들을 이용하여 특정 경혈에서 투사하는 신경계 내 표지영역들을 관찰하는 것은 침구치료의 기전을 신경해부학적으로 밝히는데 중요한 역할을 할 것으로 생각된다. 신경추적자를 이용한 연구에서는 경혈과 신경과의 관계를 신경 해부학적으로 밝히기 위하여 특정 경혈과 관련된 운동과 감각신경 세포의 영역 및 신경세포 내 신경 전달물질을 관찰하였고 3,4) 또한 서로 다른 경혈과 관련된 신경세포의 특징을 관찰하기 위하여 신경 추적자를 이용하여 다양한 연구가 진행되고 있다5) .…”
unclassified